Knock-Down of Long Non-Coding RNA ANRIL Suppresses Mouse Mesangial Cell Proliferation, Fibrosis, Inflammation via Regulating Wnt/β-Catenin and MEK/ERK Pathways in Diabetic Nephropathy - Fang, Xun; Hu, Jun; Zhou, Hongyan (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aims Our study aimed to investigate the role of long non-coding RNA ANRIL (lnc-ANRIL) knock-down in regulating cell activities, inflammation and downstream signaling pathways in mouse mesangial cellular diabetic nephropathy (DN) model.Methods The mouse mesangial cells (SV40-MES13 cells) were treated with high-glucose (HG) to construct cellular DN model. Lnc-ANRIL knock-down plasmid and control knock-down plasmid were transfected into HG-treated SV40-MES13 cells as Sh-ANRIL group and Sh-NC group respectively.Results Lnc-ANRIL expression was significantly higher in HG-treated SV40-MES13 cells compared with normal glucose-treated SV40-MES13 cells and osmotic control-treated SV40-MES13 cells. Lnc-ANRIL knock-down suppressed cell proliferation and promoted cell apoptosis in HG-treated SV40-MES13 cells. As for fibrosis, lnc-ANRIL knock-down reduced fibronectin and collagen I expressions in HG-treated SV40-MES13 cells. Besides, the expressions of supernatant tumor necrosis factor-alpha (TNF-α), monocyte chemoattractant protein-1 (MCP-1), interleukin (IL)-1β, IL-6, IL-8 and IL-18 were reduced in Sh-ANRIL group compared with Sh-NC group. Furthermore, Wnt3, β-catenin, p-MEK1 and p-ERK1 expressions were suppressed in Sh-ANRIL group compared with Sh-NC group, which suggested that lnc-ANRIL knock-down inhibited Wnt/β-catenin and MEK/ERK pathways in HG-treated SV40-MES13 cells.Conclusions Lnc-ANRIL knock-down suppresses mouse mesangial cell proliferation, fibrosis, inflammation, Wnt/β-catenin and MEK/ERK pathways in DN.
Keywords: lnc-ANRIL; diabetic nephropathy; fibrosis; inflammation; Wnt/β-catenin; MEK/ERK